The Fourth Amendment in an age of surveillance - Gray, David C. (Cambridge University Press, 2017)
The Fourth Amendment is facing a crisis. New and emerging surveillance technologies allow government agents to track us wherever we go, to monitor our activities online and offline, and to gather massive amounts of information relating to our financial transactions, communications, and social contacts. In addition, traditional police methods like stop-and-frisk have grown out of control, subjecting hundreds of thousands of innocent citizens to routine searches and seizures. In this work, David Gray uncovers the original meaning of the Fourth Amendment to reveal how its historical guarantees of collective security against threats of 'unreasonable searches and seizures' can provide concrete solutions to the current crisis. This important work should be read by anyone concerned with the ongoing viability of one of the most important constitutional rights in an age of increasing government surveillance
Title from publisher's bibliographic system (viewed on 12 May 2017)
Keywords: United States / Constitution / 4th Amendment; Searches and seizures / United States; Electronic surveillance / United States; USA